Penyuluhan Bantuan Hukum Cuma- Cuma bagi Masyarakat Tidak Mampu di Kota Singkawang - Aswandi; Soa, Alfonsus Hendri; Azizurrahman, Syarif Hasyim; Ismawati , Sri; Hermansyah; Siagian , Parulian; Herlina; Fitri Hertini , Mega; Abunawas (Divisi Riset, Lembaga Mitra Solusi Teknologi Informasi (L-MSTI), 2023)
The lack of public knowledge about Legal Aid and guarantees of public understanding regarding the Procedures for Obtaining Legal Aid that can be received free of charge by underprivileged people causes losses for the community. The aim of this writing is to obtain a clear picture of the reallife system of society, explore understanding of the law and legal problems that exist in society, and help the public obtain free understanding and assistance in resolving legal problems experienced in everyday life. The method in this writing uses empirical legal research methods. So, in this writing we found important steps to increase public awareness about people's rights and how to get access to the free legal assistance they need. Legal education about free legal aid can help people who are unable to understand people's rights and how people can take advantage of free legal aid to overcome the legal problems they are experiencing.